2014
DOI: 10.4103/0976-237x.137905
|View full text |Cite
|
Sign up to set email alerts
|

Serotype specific polymerase chain reaction identifies a higher prevalence of streptococcus mutans serotype k and e in a random group of children with dental caries from the Southern region of India

Abstract: Background:The development of dental caries has been associated with the oral prevalence of Streptococcus mutans. Four serotypes of S. mutans have been reported, namely serotype c, e, f, and k that are classified based on the composition and linkages of cell wall polysaccharides, response to physiological reactions, sero-specificity and 16s rRNA homology. Although the oral prevalence of S. mutans serotype c in Indian subjects with or without caries is known, the prevalence of the other three serotypes, e, f, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 29 publications
1
17
2
Order By: Relevance
“…The prevalence of serotype k (17.5%) reported here is higher than previously reported for Japanese (1.4–2%), Finnish (3.6%), and Thai (2–2.8%) subjects . A study of subjects from southern India reported a higher prevalence (26%) of serotype k than in those studies. However, in contrast to the Indian study , which used saliva, the present study was conducted using individual S. mutans isolates.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…The prevalence of serotype k (17.5%) reported here is higher than previously reported for Japanese (1.4–2%), Finnish (3.6%), and Thai (2–2.8%) subjects . A study of subjects from southern India reported a higher prevalence (26%) of serotype k than in those studies. However, in contrast to the Indian study , which used saliva, the present study was conducted using individual S. mutans isolates.…”
Section: Discussioncontrasting
confidence: 81%
“…A study of subjects from southern India reported a higher prevalence (26%) of serotype k than in those studies. However, in contrast to the Indian study , which used saliva, the present study was conducted using individual S. mutans isolates. It is possible that analysis of saliva samples in the Uniontown population would result in a higher prevalence of serotype k , comparable to that of the Indian study.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…All four serotypes were originally described using immunodiffusion method . Studies have already summarized the prevalence of S mutans serotypes by this approach and other traditional approaches . More recently, PCR‐based identification approaches have been developed and utilized for serotyping based on the variability in genes associated with the RGP synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 ] Plaque formation per se is conceived as a physiologically normal event, which otherwise is disrupted and removed by effective brushing techniques. However, when maintenance of oral hygiene suffers the bacterial flora within the plaque begins to mature with early and late colonizers,[ 3 4 ] which in the availability of carbohydrate rich substrates becomes preferentially populated by acidogenic and acid-tolerant species. [ 5 6 ]…”
Section: Introductionmentioning
confidence: 99%